2015
DOI: 10.1371/journal.pone.0128895
|View full text |Cite|
|
Sign up to set email alerts
|

Invasive Breast Cancer Incidence in 2,305,427 Screened Asymptomatic Women: Estimated Long Term Outcomes during Menopause Using a Systematic Review

Abstract: BackgroundEarlier studies of breast cancer, screening mammography, and mortality reduction may have inflated lifetime and long-term risk estimates for invasive breast cancer due to limitations in their data collection methods and interpretation.ObjectiveTo estimate the percentage of asymptomatic peri/postmenopausal women who will be diagnosed with a first invasive breast cancer over their next 25 years of life.MethodsA systematic review identified peer-reviewed published studies that: 1) enrolled no study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, this association did not persist after the adjustment in the final model. In a systematic review, Cutler et al (24) observed an average of cumulative breast cancer inci- Family history of breast cancer is directly associated with the disease. Having a first degree relative with breast cancer is one of the most consistent risk factors for the disease (19,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, this association did not persist after the adjustment in the final model. In a systematic review, Cutler et al (24) observed an average of cumulative breast cancer inci- Family history of breast cancer is directly associated with the disease. Having a first degree relative with breast cancer is one of the most consistent risk factors for the disease (19,25).…”
Section: Discussionmentioning
confidence: 99%
“…Menopause is a naturally occurring phenomenon that affects most women above the approximate age of 52 years. The menopause-associated physiological exhaustion of ovarian function increases reproductive, cardiovascular and mental impairments and cancer (Pluchino et al 2011, Cutler et al 2015, Gong et al 2016, Honour 2018). Furthermore, the musculoskeletal system is also deeply affected by menopause (Cauley 2015, Sullivan et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 19 studies comprising over two million asymptomatic women found that invasive breast cancer rates may be lower for those who do not opt for mammograms, since these unscreened women are not overdiagnosed. 19 Furthermore, lesions that are highly localized in situ and are not necessarily clinically relevant are not detected in these unscreened women. Two thirds of breast cancers found by mammography are overdiagnosed, with the majority not developing into clinical disease.…”
Section: Breast Cancermentioning
confidence: 99%